Ion‐selective electrodes to monitor osteoblast‐like cellular influence on the extracellular concentration of calcium. (27th April 2012) - Gustavsson, J.; Planell, J.; Engel, E.
Abstract: In bone tissue engineering, the composition of the ionic extracellular environment (IEE) can determine both cellular fate and a biomaterial's development and performance. Therefore, precise control of the IEE and a perfect understanding of the dynamic changes that it can be subject to due to cellular activity is highly desired. To achieve this, we initially monitored how two standard osteoblast‐like cell models that expressed either high or low alkaline phosphatase activity ‐ SAOS‐2 and MG63 cells, respectively ‐ affected the extracellular concentrations of calcium and phosphate during long‐term cultures. It was observed that cellular influence on the IEE varied greatly between the two models and could be linked to the capacity of cells to deposit calcium in the extracellular matrix. Miniaturized ion‐selective electrodes that could allow for real‐time monitoring of calcium in a minimally invasive way were then constructed. The electrodes were characterized in standard in vitro cell culture environments, prior to being successfully applied for periods of 24 h, to record the dynamics of cell‐induced deposition of calcium in the extracellular matrix, while using osteogenic media of either high or low concentrations of phosphate. As a result, this study provides the background and technological means for the non‐destructive evaluation of the IEE in vitro and allows for the optimization and development of better models of bone tissue construction. Copyright © 2012 John Wiley & Sons, Ltd.